Validation of the Angioedema Control Test (AECT)-A Patient-Reported Outcome Instrument for Assessing Angioedema Control - Weller, Karsten; Donoso, Tamara; Magerl, Markus; Aygören-Pürsün, Emel; Staubach, Petra; Martinez-Saguer, Inmaculada; Hawro, Tomasz; Altrichter, Sabine; Krause, Karoline; Siebenhaar, Frank; Metz, Martin; Zuberbier, Torsten; et al. (The journal of allergy and clinical immunology in practice (Cambridge, MA), 2020)
Recurrent angioedema (RA) is an important clinical problem in routine care and emergency medicine. As of recently, the only validated tools to specifically assess disease status in patients with RA were diary-type activity assessments and angioedema-related quality-of-life questionnaires. Although these tools are particularly helpful in clinical studies, they were not designed to determine disease control or to guide treatment decisions. To close this gap, the Angioedema Control Test (AECT) was published recently. To test the AECT for its validity and reliability, and to identify a cutoff value to aid treatment decisions. Two AECT versions with a recall period of 4 weeks (AECT-4wk) and 3 months (AECT-3mo) were tested for their internal consistency and test-retest reliability, convergent and known-groups validity as well as screening accuracy in 81 patients with RA with bradykinin-mediated angioedema, mast cell mediator-mediated angioedema, or idiopathic angioedema. Both AECT versions showed excellent internal consistency reliability with a Cronbach alpha value of more than 0.85 and test-retest reliability with an intraclass correlation coefficient greater than 0.9. The convergent validity of both AECT versions was high. Both tools showed strong correlations with anchors of disease control, angioedema frequency, and health-related quality of life. A stratification of AECT scores into different levels of disease control together with a receiver-operating characteristic curve analysis suggested a cutoff value of 10 or more points to identify patients with well-controlled RA versus less than 10 points to identify patients with poorly controlled disease for both AECT versions. The AECT is the first valid and reliable patient-reported outcome measure to assess disease control in patients with RA.